First digital study of the frontal sinus of stem-Canini (Canidae, Carnivora): evolutionary and ecological insights throughout advanced diagnostic in paleobiology - Frosali, Samuele; Bartolini-Lucenti, Saverio; Madurell-Malapeira, Joan; Urciuoli, Alessandro; Costeur, Loïc; Rook, Lorenzo (Frontiers in Ecology and Evolution, 2023)
The phylogenetic and ecological importance of paranasal sinuses in carnivorans was highlighted by several previous authors, mostly in extant species. Nevertheless, no specific study on this feature on extant canids, and no one on fossil representatives of the family, has been published up to now. Here, we analyze for the first time the paranasal sinus of extant and fossil canids through computed tomographic techniques to characterize them morphologically and morphometrically, making ecological inferences. To do so, we applied for the first time an innovative deformation-based morphometric approach. The results obtained for extant species highlight a remarkable correlation between morphology and ecomorphotypes previously defined by some scholars (namely hypercarnivorous group-hunters; small-prey hypercarnivores, mesocarnivores, hypocarnivores). Our results thus support the direct relationship between diet preferences and the development of frontal sinus in canids. Regarding fossil specimens, we reconstructed for the first time the frontal sinus of three Eucyon species and compared it to those of living forms. The best-preserved specimen, the only known cranium of Eucyon adoxus dated to the Late Pliocene of Saint-Estève (France), displayed similarities with hypercarnivorous group-hunter canids by the large sinus prominences. Given that the overall craniodental morphology of E. adoxus suggests that it acted as a small prey hypercarnivore—similar to extant Canis simensis—the aforementioned affinities might have evolved independently, in relation to high stresses during feeding. Overall, our study demonstrates that morphological inspection and deformation-based geometric morphometrics complement each other and allow a thorough investigation of sinus shape variability, thus enabling the study of sinus morphology in other fossil carnivorans with the ultimate goal of inferring their ecological preferences.